René Girard on terrorism: "We have to radically change the way we think." Have we? - Haven, Cynthia L. (2015)
Today is the funeral of René Girard, the renowned French theorist who taught us so much about violence (a larger memorial service will also be held in January at Stanford Memorial Church). It is also a day of national mourning in France, which yesterday suffered a terrorist attack of an unprecedented scale, the biggest attack on […]